1993
DOI: 10.1128/aac.37.10.2235
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of host cell invasion and intracellular replication of Trypanosoma cruzi by N,N'-bis(benzyl)-substituted polyamine analogs

Abstract: We studied the effects of two N,N'-bis(benzyl)-substituted polyamine analogs on the capacities of Trypanosoma cruzi to invade and multiply within a mammalian host cell. At concentrations as low as 1 ,uM, these compounds reduced significantly the infectivity of the parasite for rat heart myoblasts in a time-dependent manner. Pretreatment of virulent T. cruzi trypomastigotes, but not myoblast pretreatment, reduced the level of infectivity. The inhibitory effects started to subside 3 h after removal of the drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…However, when we quantified parasite loads on infected-MΦs activated with 25% of iSN, we observed that DFMO treatment was detrimental for the proliferation of intracellular parasites at 72 h post-infection (Figure 4F). This finding may indicate that polyamine synthesis is a requirement for parasite proliferation and maintenance in these conditions, as described in other models (Majumder and Kierszenbaum, 1993; Vannier-Santos et al, 2008). Nevertheless, our data imply that PS exposure on intracellular amastigotes is modulated by cytokine-mediated, iNOS-dependent MΦ activation, rather than by arginase I expression.…”
Section: Resultssupporting
confidence: 73%
“…However, when we quantified parasite loads on infected-MΦs activated with 25% of iSN, we observed that DFMO treatment was detrimental for the proliferation of intracellular parasites at 72 h post-infection (Figure 4F). This finding may indicate that polyamine synthesis is a requirement for parasite proliferation and maintenance in these conditions, as described in other models (Majumder and Kierszenbaum, 1993; Vannier-Santos et al, 2008). Nevertheless, our data imply that PS exposure on intracellular amastigotes is modulated by cytokine-mediated, iNOS-dependent MΦ activation, rather than by arginase I expression.…”
Section: Resultssupporting
confidence: 73%
“…Future studies with the best candidates will focus on elucidating mode of action. The fact that similar compounds act by different mechanisms in trypanosomatids [22,47] and the pathogenic fungus Pneumocystis carinii [48] support this hypothesis. Polyamine oxidase have been studied as a possible target of MDL-27695 on P. falciparum [49].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro MIC 50 of 3.0 M was reported for the human malaria parasite (18). Exposure of mammal-infective T. cruzi trypomastigotes to 1 M BBS prior to adding to mammalian cells caused a 61% reduction in the number of infected mammalian cells and a 69% reduction in the mean number of parasites per infected cell compared to untreated control trypomastigotes (11). When T. cruzi was already growing in mammalian cells, a 24-h exposure to 1 M BBS caused a 41% reduction in parasite multiplication, compared to untreated controls.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here show that a polyamine analogue, BBS, is also active against PCP and provide information about the interaction of this analogue and P. carinii. The choice of BBS for the study was based on previous reports of activity against Plasmodium, the malaria parasite, about 10 years ago (7) and subsequent reports of activity against the protozoans Leishmania donovani (1) and Trypanosoma cruzi (11), as well as the filarial parasite Brugia pahangi (19). A summary of previous results with BBS and other parasites is presented below to provide perspective for the results presented here.…”
Section: Discussionmentioning
confidence: 99%